Optimization of planning radionuclide diagnostic tests in osteoscintigraphy - N. A. Maksimova; V. G. Karpun; M. A. Arzamastseva; M. G. Ilchenko; O. S. Shlyk (Южно-Российский онкологический журнал, 2021)
Purpose of the study. Determining maximum possible number of high-quality radionuclide studies by days of the generator operation.Materials and methods. We studied the factors influencing the capacity of radionuclide diagnostic tests in osteoscintigraphy (OSG) by days of service life of a 99mTc generator GT-4K. The OSG capacity, the required resource of 99mTc and its efficiency in OSG were calculated. The optimal days for the generator delivery were determined.The Pirfotech 99mTc radiopharmaceutical (RFP) prepared with the generator was used for OSG.Scanning, data collection and processing of results were carried out on gamma-cameras of the systems Signature Series, Symbia T16 Siemens, and syngo M1 Applications VB10 Siemens.Parameters of the radioactivity of 99mTc were processed by mathematical methods using the Excel program.Results. We revealed specific factors influencing the OSG capacity: 1) three-hour accumulation of RFP after its administration to the patient; 2) generator activity by days of its operation; 3) the day of the week of the generator delivery. We calculated quantitative indicators of the maximum possible OSG capacity during the generator operation (maximum number of OSG procedures by days of operation, total capacity, preferred day of the week for the generator delivery).Conclusion. The most significant factors in optimal OSG planning by days of the generator operation are the generator specifications, quantity and frequency of generator supply, provision of gamma-cameras.The described technique for scheduling diagnostic procedures can be useful for the efficient use of the generator system which ensures the maximum amount of high-quality RFP from the generator eluate and contributes to the objectification of the cancer process in order to choose the treatment tactics.